Extract of a polyherbal formulation ameliorates experimental nonalcoholic steatohepatitis - Azeemuddin, Mohammed (J Tradit Complement Med, 2015)
The objective of the present study is to evaluate the effect of the extract of a well-known hepatospecific polyherbal formulation, Liv.52, in an experimental model of high-fat diet (HFD)-induced nonalcoholic steatohepatitis (NASH) in rats. Feeding a HFD for 15 weeks resulted in significant impairment of the lipid profile, elevation of hepatic enzyme markers, and insulin resistance in rats. The histological examination of the liver furthermore indicated fibrotic changes and fat deposition in hepatic tissues. The treatment with Liv.52 extract [125 mg/kg body weight per os (b.wt. p.o.)], which was administered from week 9 onward, reversed the HFD-induced changes to a statistically significant extent, compared to the untreated positive control animals. The effect observed with Liv.52 extract was comparable to that of pioglitazone (4 mg/kg b.wt.), a standard drug that is useful in the management of NASH. The treatment with Liv.52 extract significantly reduced steatosis, collagen deposition, and necrosis in hepatic tissues, which indicates its antifibrotic and antinecrotic properties. The results obtained in the present set of experiments indicate that Liv.52 extract effectively reverses metabolic and histological changes associated with HFD-induced NASH.